Earthquake Risk and Disaster Financing Analysis of Basarnas Buildings in Bengkulu City: English - Hesri Marlina Hesti; Dina Ruslanjari; Teuku Faisal Fathani; Muslikun Sodik (Jagratara: Journal of Disaster Research, 2026)
Disaster insurance has become one of the alternative financing mechanisms for damage to state-owned buildings. Financing through insurance is expected to accelerate post-disaster recovery and reduce dependence on the APBN. However, not all buildings are eligible for insurance coverage. Disaster hazards, building vulnerability, and building function are the primary considerations in determining insurance priorities. This study aims to estimate the seismic vulnerability level of buildings at the Bengkulu Search and Rescue Office (Basarnas) and to analyze an optimal disaster risk financing scheme based on probable building losses. Building vulnerability was assessed using the FEMA P-154 Rapid Visual Screening (RVS) method, and disaster risk financing was determined through a comparative analysis of government-borne rebuilding costs and the corresponding insurance premiums. The results indicate that the Bengkulu Search and Rescue Office building has a low level of vulnerability. The building is potentially subject to minor damage to structural components and moderate damage to non-structural components. Meanwhile, the cost analysis shows that the annual insurance premium is approximately 70% lower than the estimated rebuilding cost. Therefore, disaster risk financing through insurance is considered more appropriate for the research object.